CuCo2O4 ORR/OER Bi-Functional Catalyst: Influence of Synthetic Approach on Performance. Issue 4 (7th February 2015) - Serov, Alexey; Andersen, Nalin I.; Roy, Aaron J.; Matanovic, Ivana; Artyushkova, Kateryna; Atanassov, Plamen
Abstract : A series of CuCo2 O4 catalysts were synthesized by pore forming, sol-gel, spray pyrolysis and sacrificial support methods. Catalysts were characterized by XRD, SEM, XPS and BET techniques. The electrochemical activity for the oxygen reduction and oxygen evolution reactions (ORR and OER) was evaluated in alkaline media by RRDE. Density Functional Theory was used to identify two different types of active sites responsible for ORR/OER activity of CuCo2 O4 and it was found that CuCo2 O4 can activate the O-O bond by binding molecular oxygen in bridging positions between Co or Co and Cu atoms. It was found that the sacrificial support method (SSM) catalyst has the highest performance in both ORR and OER and has the highest content of phase-pure CuCo2 O4 . It was shown that the presence of CuO significantly decreases the activity in oxygen reduction and oxygen evolution reactions. The half-wave potential (E1/2 ) of CuCo2 O4 -SSM was found as 0.8 V, making this material a state-of-the-art, unsupported oxide catalyst.